Studi Kelayakan Investasi Sistem PLTS Atap On-Grid 3 kWp Pada Gedung PT Lisensi - Rahmat Hidayat Hamidi; Linda Faridah; Andri Ulus Rahayu (Universitas Dirgantara Marsekal Suryadarma, 2026)
The growing demand for electricity in Indonesia is driving the use of renewable energy sources through the implementation of rooftop solar power plants (PLTS). Research on grid-connected solar power plants generally focuses on large-scale systems, while studies on small-scale systems for office buildings remain limited. This study aims to analyze the technical and economic feasibility of a 3 kWp on-grid rooftop SPP system at the PT Lisensi building. The research method employs a descriptive quantitative approach through the collection of electricity load data, simulation using PVsyst software, and economic analysis using the Life Cycle Cost (LCC), Net Present Value (NPV), Profitability Index (PI), Discounted Payback Period (DPP), and Break-Even Point (BEP) methods. Simulation results indicate an annual energy production of 4,475.8 kWh, meeting approximately 78% of the building’s electricity needs. The economic analysis results show an NPV of Rp48,829,240, a PI > 1, a DPP of 7.4 years, and a BEP in the 6.9th year. Based on these results, a 3 kWp on-grid rooftop solar power system is technically and economically feasible for small-scale office buildings